Potential for Nitrogen Fixation and Nitrification in the Granite-Hosted Subsurface at Henderson Mine, CO - Swanner, Elizabeth; Templeton, Alexis (Frontiers in Microbiology, 2011)
The existence of life in the deep terrestrial subsurface is established, yet few studies have investigated the origin of nitrogen that supports deep life. Previously, 16S rRNA gene surveys catalogued a diverse microbial community in subsurface fluids draining from boreholes 3000 feet deep at Henderson Mine, CO (Sahl et al., 2008). The prior characterization of the fluid chemistry and microbial community forms the basis for the further investigation here of the source of NH4+. The reported fluids chemistry included N2, NH4+ (5-112 μM), NO2- (27-48 μM) and NO3- (17-72 μM). In this study, the correlation between low NH4+ concentrations in dominantly meteoric fluids and higher NH4+ in rock-reacted fluids is used to hypothesize that NH4+ is sourced from NH4+-bearing biotite. However, biotite samples from the host rocks and ore-body minerals were analyzed by Fourier Transform Infrared (FTIR) microscopy and none contained NH4+. However, the nitrogenase-encoding gene nifH was successfully amplified from DNA of the fluid sample with high NH4+, suggesting that subsurface microbes have the capability to fix N2. If so, unregulated nitrogen fixation may account for the relatively high NH4+ concentrations in the fluids. Additionally, the amoA and nxrB genes for archeaeal ammonium monooxygenase and nitrite oxidoreductase, respectively, were amplified from the high-NH4+ fluid DNA, while bacterial amoA genes were not. Putative nitrifying organisms are closely related to ammonium-oxidizing Crenarchaeota and nitrite-oxidizing Nitrospira detected in other subsurface sites based upon 16S rRNA sequence analysis. Thermodynamic calculations underscore the importance of NH4+ as an energy source in a subsurface nitrification pathway. These results suggest that the subsurface microbial community at Henderson is adapted to the low nutrient and energy environment by their capability of fixing nitrogen, and that fixed nitrogen may support subsurface biomass via nitrification.